Compliance como ferramenta de governança pública para a efetividade do estado: estudo de caso no estado do Paraná - Souza Filho, Gilberto Antonio de (2022)
Corruption scandals generated a revolt in the Brazilian population against public institutions, giving strength to the theme of fighting corruption and developing institutional designs to prevent deviations. In this scenario, the State of Paraná instituted the Integrity and Compliance Program through State Law 19.857/2019. This dissertation is proposed to contribute to the development of best management and public governance practices by evaluating the institutional design mentioned, according to the main international methodologies, identifying vulnerabilities and proposing improvements. For this, the applied research strategy, qualitative, exploratory by bibliographic research and descriptive by documental research, ex-post-facto and natural participant research will be used methodologically. It is expected, with this, to identify the possible vulnerabilities of the instituted design and, thus, to propose adjustments and improvements.